Domain Organization of the UBX Domain Containing Protein 9 and Analysis of Its Interactions With the Homohexameric AAA + ATPase p97 (Valosin-Containing Protein) - Riehl, Jana; Rijal, Ramesh; Nitz, Leonie; Clemen, Christoph S.; Hofmann, Andreas; Eichinger, Ludwig (Frontiers in Cell and Developmental Biology, 2021)
Using three independent approaches, we probed the UBXD9 interactome in Dictyostelium discoideum and identified novel interaction partners, including glutamine synthetase type III as well as several actin-binding proteins, suggesting that UBXD9 may have a function in the organisation of the actin cytoskeleton. The experimental approaches used in this study further confirmed p97 (also known as valosin-containing protein, VCP) as an interaction partner of UBXD9. p97 is an abundant homohexameric AAA+ ATPase, which is highly conserved from D. discoideum to human. Owing to its fundamental function in protein quality control pathways, where it catalyses the unfolding of proteins, p97 is implicated in almost every area of cell physiology, thus rendering it a pivotal factor of cellular protein homeostasis. Its regulation is subject to more than 30 cofactors with which p97 forms higher order complexes. The largest family of cofactors is the UBXD protein family, whose members all carry an Ubiquitin Regulatory X (UBX) domain that enables binding to p97. Here, we analysed one member of this family, the largely uncharacterised UBXD9 protein. Based on the domain structure of UBXD9, we expressed and purified a series of N- and C-terminal truncation constructs and characterised their interactions with p97. Pull-down assays revealed that the UBX domain (amino acids 384–466) is necessary and sufficient for a strong interaction with p97. An N terminal extension of the UBX domain, which folds into a β0 α-1 α0 lariat structure, is required for the dissociation of p97 hexamers. This dissociation is reflected in a strongly reduced ATPase activity of p97 upon addition of full length UBXD9 or UBXD9261–573 to p97 hexamers. Blue Native PAGE and structural model prediction suggest that hexamers of UBXD9 or UBXD9261–573 interact with p97 hexamers and disrupt the p97 subunit interactions via insertion of a helical lariat structure, presumably by destabilising the p97 D1:D1’ intermolecularc interface. In conclusion, we propose that UBXD9 influences p97 activity in vivo by shifting the equilibrium from hexamers to monomers.